1990
DOI: 10.1111/j.1348-0421.1990.tb01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescence Response of Human Phagocytes against IgG‐Opsonized Staphylococci with and without Protein A Activities

Abstract: The effects of immunological IgG binding to Staphylococcus aureus and IgG binding via protein A on the chemiluminescence (CL) response of human phagocytes were examined. The results obtained by enzyme immunoassay showed a clear correlation between the magnitude of the CL response and amount of IgG on protein A-deficient HL-87 strain. Despite no difference in protein A activity between 209P and Cowan I strains, the CL response to IgG-opsonized 209P cells was lower than that to Cowan I cells similarly opsonized.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
4
1
2
Order By: Relevance
“…We previously reported that IgG bound to protein A via its Fc portion had no significant effect on the phagocytic CL response (26). However, we did not obtain any clear evidence for any effect of protein A on the interaction between the bacteria and phagocytes without opsonins.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…We previously reported that IgG bound to protein A via its Fc portion had no significant effect on the phagocytic CL response (26). However, we did not obtain any clear evidence for any effect of protein A on the interaction between the bacteria and phagocytes without opsonins.…”
Section: Discussioncontrasting
confidence: 91%
“…Hemagglutination (HA) test. Protein A activity was quantitatively assayed by a previously reported method (22,(24)(25)(26). Briefly, two-fold serial dilutions (100 pl.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations